2006
DOI: 10.2224/sbp.2006.34.2.181
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Between Coping Strategies and Depression Among Turkish Adolescents

Abstract: The relationships between coping strategies and depression were examined in a sample of 543 Turkish adolescents using a Turkish version of the Coping Across Situations Questionnaire (Seiffge-Krenke, 1995). MANOVA results revealed significant main effects for gender, school type and grade level in coping strategies. Females compared to males and adolescents from state high schools compared to adolescents from Anatolian high schools used higher levels of approach-oriented coping. Males compared to females, adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
0
7
0
5
Order By: Relevance
“…28 Another factor could be the gender difference of coping style, males are more likely than females to use avoidance strategies and emotional distraction coping, thus might be more likely to go with online-related activities such as online gaming to avoid the problems or stressors. 29 Studies also found that more males than female play online games to pursue feelings of achievement and enhance self-image by offering opportunities to interact with others sharing the same interest and to pursue a strong and smart self-identification, both of which increase the risk of addiction among males. 30 On the contrary, female were more prone to the risk of addicted to social networking as they used the platform to maintain relationships and present themselves as attractive and part of a social group.…”
Section: Discussionmentioning
confidence: 99%
“…28 Another factor could be the gender difference of coping style, males are more likely than females to use avoidance strategies and emotional distraction coping, thus might be more likely to go with online-related activities such as online gaming to avoid the problems or stressors. 29 Studies also found that more males than female play online games to pursue feelings of achievement and enhance self-image by offering opportunities to interact with others sharing the same interest and to pursue a strong and smart self-identification, both of which increase the risk of addiction among males. 30 On the contrary, female were more prone to the risk of addicted to social networking as they used the platform to maintain relationships and present themselves as attractive and part of a social group.…”
Section: Discussionmentioning
confidence: 99%
“…Bazı stresle başa çıkma tarzları stresle ilişkili negatif duyguları düzenleyerek alternatif çözümler üreten koruyucu bir işlev olarak yardım edebilir, bazen de stresin etkilerini kötüleştirerek uyum sorunlarına yol açabilir [53]. Kişinin stresle baş etme becerisi anksiyete ve depresyonun belirleyici olarak düşünülebilir.…”
Section: Discussionunclassified
“…Bazen stresle başa çıkma yöntem-leri stresle ilişkili negatif duyguları düzenleyerek alternatif çözümler üreten koruyucu bir işlev olarak yardım edebilir, bazen de stresin etkilerini kötüleştirerek uyum sorunlarına yol açabilirler. [30] Bu araştırmada öğrencilerin SBTÖ toplam puanı 77.88±10.08 ve alt ölçeklerinden aldıkları puanlar ise, problem çözme 27.23±4.08, sosyal destek arama 26.28±4.06, kaçınma 24.36±4.01 olarak belirlenmiştir. Öğrenciler en fazla pozitif başetme yöntemlerinden probleme yönelik çözüm yöntemlerini kullandıkları saptanmıştır.…”
Section: Sosyal Destek Aramaunclassified